2019
DOI: 10.3390/s19235169
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Home-Monitoring Sensor Technology in Patients with Parkinson’s Disease—Acceptance and Adherence

Abstract: Parkinson’s disease (PD) is characterized by a highly individual disease-profile as well as fluctuating symptoms. Consequently, 24-h home monitoring in a real-world environment would be an ideal solution for precise symptom diagnostics. In recent years, small lightweight sensors which have assisted in objective, reliable analysis of motor symptoms have attracted a lot of attention. While technical advances are important, patient acceptance of such new systems is just as crucial to increase long-term adherence.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
31
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 35 publications
(56 reference statements)
2
31
2
Order By: Relevance
“…Consistent with recent findings [ 38 ], the overall feasibility and high acceptance of the insole-based pressure sensor for walking and FoG assessment should be highlighted. They should be considered as an effective tool in telemedicine and suitable for home-based clinical assessment with simple tests used to assess patients’ walking and freezing.…”
Section: Discussionsupporting
confidence: 83%
“…Consistent with recent findings [ 38 ], the overall feasibility and high acceptance of the insole-based pressure sensor for walking and FoG assessment should be highlighted. They should be considered as an effective tool in telemedicine and suitable for home-based clinical assessment with simple tests used to assess patients’ walking and freezing.…”
Section: Discussionsupporting
confidence: 83%
“…In addition, we also observed that wearable sensors were also in use in combination with ambient sensors in 10 included papers. The wearable devices are frequently embedded with accelerometers [ 69 , 75 , 76 ] and radio-frequency identification (RFID) tags [ 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…Some cases, however, involved wearable sensors as well. For instance, activity monitoring task frequently adopts wearable accelerometers, which can deliver more precise results (e.g., activity level) than ambient sensors [ 69 , 75 , 76 ]. RFID tag may address the issue of distinguishing multiple individuals under monitoring [ 44 ], especially when cameras are absent.…”
Section: Discussionmentioning
confidence: 99%
“…A recent review analyzed the validation, feasibility, clinical outcomes, and costs of 13 different wearable devices and concluded that these were predominantly in the validation and feasibility testing phases [ 31 ]. Despite the exponential growth in wearable technology, little evidence is available regarding wearability and acceptance in the clinical setting [ 30 , 32 , 33 ]. We note that, for all the devices under test, only the VitalPatch had indexed wearability studies available [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%